Trade-offs between xylem hydraulic efficiency and mechanical strength in Chinese evergreen and deciduous savanna species - Zhang, Shu-Bin; Wen, Guo-Jing; Qu, Ya-Ya; Yang, Lin-Yi; Song, Yu (Tree physiology, 2022)
Abstract Evergreen and deciduous species coexist in tropical dry forests and savannas, but differ in physiological mechanisms and life-history strategies. Hydraulic conductivity and mechanical support are two major functions of the xylems of woody plant species related to plant growth and survival. In this study, we measured sapwood-specific hydraulic conductivity (Ks), leaf-specific hydraulic conductivity (KL), modulus of rupture (MOR) and elasticity (MOE), xylem anatomical traits and fiber contents in the xylems of 20 woody species with contrasting leaf phenology (evergreen vs deciduous) in a Chinese savanna. Our results showed that deciduous species had significantly higher Ks and KL but lower MOR and MOE than evergreen species. Evergreen species experienced more negative seasonal minimum water potential (Pmin) than deciduous species during the dry season. Furthermore, we found trade-offs between xylem hydraulic efficiency and mechanical strength across species and within the evergreen and deciduous groups, and these trade-offs were modulated by structural and chemical traits. Both Ks and KL were significantly related to hydraulic weighted vessel diameter (Dh) across all species and within the deciduous group. Both MOR and MOE were significantly related to wood density, neutral detergent fiber and acid detergent fiber across species and within evergreen and deciduous groups. Our findings demonstrated that Chinese evergreen and deciduous savanna species diverged in xylem hydraulic and mechanical functions, reflecting conservative and acquisitive life-history strategies for evergreen and deciduous species, respectively. This study provides new information with which to understand the hydraulic and biomechanical properties and ecological strategies of savanna species in long-term dry-hot environments.